Hubungan antara Organisational Citizen Behavior dengan Burnout - A Anggawira; A Andhika (Psyche 165 Journal, 2019)
The study objective was to determine correlation between organizational citizen behaviour (ocb) and burnout of employee at PT. Kunango Jantan Padang. This research used survey method and the analaysis used correlation techniques. Sample Size of 55 employee obtained by saturation sampling technique. The instrument used was aquestionaire to measure stress by Maslach Burnout Inventory and ocb by likert scale’s wiranti (2007). The result shown 40% employee has indicated have potentially to be burnout, and 58,18 % employee has middle range on OCB. Result of the hypothesist namely there is positive correlation between OCB and Burnout but they don’t have enough significant’s value.